EVALUATION OF THE PHYSICAL AND RHEOLOGY PROPERTIES OF RUBBERIZED ASPHALT CEMENT - Salih, Anmar H.; Hussain, Hussain Dhafir (Journal of Applied Engineering Science, 2022)
Asphalt cement is a viscoelastic substance that operates like an elastic solid at low service temperatures or under rapid loading. Whenever loaded slowly or at high temperatures, it behaves like a viscous liquid. This classic duality necessitates enhancing the efficiency of an asphalt binder to decrease stress cracking at cold temperatures (fatigue) and plastic deformation at hot temperatures (rutting). The use of polymer-modified asphalt binder is one solution for satisfying today's pavement performance standards. The purpose of this study was to determine the impact of asphalt cement modifiers on the physical and rheological properties of asphalt cement. This study used asphalt cement with a penetration grade of 40-50, modified with styrene-butadiene rubber (SBR) at four different levels of modification, specifically 0%, 2%, 4%, and 6% by weight of asphalt cement. Depending on Rotational viscosity and dynamic shear rheometer, and the traditional test. The mixes modified with SBR polymer showed enhanced physical and rheology characteristics, with decreased penetration and ductility and increased viscosity and softening point, as well as a lower rutting factor, indicating an increase in rutting resistance, according to the experimental data. The performance grade for original asphalt cement was 64-16, and for SBR at 2% additive, the original PG was improved to PG70-16. Adding 4% additive to asphalt cement improved the performance grade to PG76-16, and using 6% increased the performance grade to PG82-16.
Keywords: rheology, physical, SBR, dynamic shear rheometer, viscosity